Mechanical Properties of Glass Fiber Reinforced Polymer Bars After Exposure to Elevated Temperatures - (:unkn) unknown (My University, 2014)
ABSTRACT MECHANICAL PROPERTIES OF GLASS FIBER REINFORCED POLYMER BARS AFTER EXPOSURE TO ELEVATED TEMPERATURES by Mohammed A. J. Alsalihi The University of Wisconsin-Milwaukee, 2014 Under the Supervision of Professor Habib Tabatabai In the past few decades, the use of composite materials has become more widespread in different fields and industries. Part of this increase comes as an answer to the corrosion issues that ordinary steel faces. Fiber Reinforced Polymers (FRP)s offer a number of advantages that make them an adequate solution to challenges in the rapidly developing construction industry. However, the behaviors of these materials at elevated temperatures and their post-exposure properties are not sufficiently investigated and understood. In this work the mechanical properties of glass fiber reinforced polymer (GFRP) bars are studied after exposure to elevated temperatures at different durations. The variation of the modulus of elasticity, tensile failure strain, and tensile strength are investigated. The study included tests of 64 dog-bone-shaped GFRP test specimens, as well as 10 full-size GFRP bars, where the specimens were subjected to elevated temperatures of up to 350oC at different exposure durations of up to 30 minutes. In most cases, the post-heat tensile strength of GFRP dog-bone specimens was reduced with longer durations of heating exposure. However these reductions were less than 10%. Little variation was observed in the post-heat modulus of elasticity of GFRP samples heated to elevated temperatures in the range of 250oC to 350oC, and for durations of heating not longer than 30 minutes. Some of the samples heated to 350oC exhibited pseudo-ductile failure patterns.
Keywords: Elevated Temperatures; GFRP; Glass Fiber Reinforced Polymer; Mechanical Properties; Pseudo-Ductility